ANALISIS FAKTOR RISIKO MEROKOK, STRES DAN RIWAYAT KELUARGA YANG BERHUBUNGAN DENGAN KEJADIAN PENYAKIT JANTUNG KORONER - I Putu Sudayasa; Sjarif Subijakto; Wa Ode Asfiyai Sahrul (Halu Oleo University, 2014)
Heart disease is the number one cause of death in the world, including Indonesia. According to the World Health Organization (WHO), 60 % of all causes of death of heart disease are coronary heart disease (CHD). Coronary heart disease can attack at reproductive age and cause of sudden cardiac arrest and death. This study aims to determine smoking, stress and family history are risk factors associated with the incidence of coronary heart disease. This research is an observational analytic study with case control design. This research was done at the General Hospital Bahteramas Southeast Sulawesi Province in February-March 2014. Sample in this study consisted of 49 respondents of cases and 49 respondents of controls were taken by purposive sampling with matching on age, sex, blood pressure, dyslipidemia, diabetes mellitus, body mass index and history of alcohol consumption. Data collection using medical records and questionnaires. The statistical test using odds ratio with 95% confidence intervals. The results showed that smoking is a risk factor associated with the incidence of coronary heart disease (OR = 2.450, 95 % CI = 1.050 - 5.713), stress is a risk factor that is associated with the incidence of coronary heart disease (OR = 6.250, 95 % CI = 2.353 -16.598) and family history are risk factors associated with the incidence of coronary heart disease (OR = 9.4, 95 % CI = 2.005 - 44.061). Smoking, stress and family history are risk factor associated with coronary heart disease with opportunities respectively at 2,4 times, 6,2 times and 9,4 times compared with control population.Keywords : Coronary Heart Disease, Smoking, Stress, Family History, Premature CAD